Exploring The Potential of Mango Seed as A Bioadsorbent for Pb(II) Removal in Aqueous Solution - Zakaria, Ahmad; Aynuddin, Aynuddin; Djasmasari, Wittri (Syarif Hidayatullah State Islamic University, 2023)
Various industrial activities produce heavy metals as by-products or wastes. Lead is a metal trace element from sewage disposal, vehicle fumes, and atmospheric emissions from industrial activities. Mango seeds are composed of cellulose, lignin, and hemicellulose, which have many potential binding groups. Mango seeds, which are often considered waste, can be utilized as a low-cost biosorbent due to their various functional groups, such as hydroxyl, carboxyl, carbonyl, alcohol, amide, and aromatic groups. Mango seed are organic waste with potential as low-cost biosorbent for heavy metals removal. The purposes of the study are: (1) to explore the optimum condition of biosorbent in absorbing heavy metal species (Pb (II)), and (2) to analyze the adsorption model of synthetic waste containing Pb(II). Mango seeds have a considerable potential to be used as a biosorbent to absorb heavy metal ions. The optimum conditions for Pb2+ ion adsorption is at pH 6 with contact time 70 minutes, and concentration of biosorbent 2.0 g/L. Adsorbate adsorption follows the Freundlich model, and adsorption occurs only in a few surface layers. The kinetic parameters of adsorbent satisfied pseudo-second-order reaction. The optimum adsorption capacity (qm) of mango seed biosorbent in absorbing Pb ions is 43.86 mg/g.